RATIONAL PHARMACOTHERAPY BASED ON PHARMACOECONOMIC DATA AUDIT: PRINCIPLES AND APPLICATION IN BULGARIA - T. Vekov (Столичная издательская компания, 2015)
The theoretical foundations of the application of pharmacoeconomic evaluations of pharmacotherapies in order to improve their economic efficiency and support the process of taking decisions on their payment from public funds are examined. An algorithm is presented for the pharmacoeconomic audit, which is applicable for assessing the objectivity and reliability of the proposed pharmacoeconomic data from pharmaceutical manufacturers in the application process for inclusion in the positive list of medicines in Bulgaria and the reimbursement of economically rational pharmacotherapies from the public health fund.